Humanitarian Teachings of Christianity and Islam - hanif, abdurrohman; arya, diaz; valentino, deva; wibowo, ganang; abdurrazaq, nizar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The aim of this research is to provide insight into the concept of humanitarian teachings in Christianity and Islam as a basis for understanding ethical values, social solidarity and contribution to the development of human welfare. By focusing on the two major religions, Christianity and Islam, it provides a comprehensive overview of the similarities, differences, and potential contributions to humanitarian teachings of the two. In the context of Christianity, it teaches the concepts of love, mercy and social responsibility found in the Bible. Meanwhile, Islam teaches the concept of brotherhood, justice and a caring society. The method used is text analysis, literature studies, and interviews with religious scholars to gain in-depth insight. It is hoped that these results will provide a better understanding of Christianity and Islam.